Improving access to healthcare services for sickle cell disease patients in Nigeria: perspectives and views of healthcare professionals - Onavbavba, Godspower; Adigwe, Obi Peter; Onoja, Solomon Oloche (Frontiers in Health Services, 2025)
IntroductionIn sub-Saharan Africa, the burden of sickle cell disease remains high. With annual sickle cell births of about 150,000, Nigeria is reported to have the highest prevalence of the disease globally. This study aimed to explore the views and perspectives of healthcare professionals regarding access to healthcare services for sickle cell disease.MethodsA quantitative cross-sectional design was employed for this study. Participants comprised healthcare practitioners across Nigeria. A well-structured questionnaire was utilised for data collection. A stratified multistage sampling strategy was used for the study, and respondents were recruited from all the six geographical zones in the country. Data collected were entered into Statistical Package for Social Sciences (SPSS) software version 25. Descriptive and inferential statistical analyses were undertaken. Results were presented in frequencies and percentages.ResultsThe response rate was 83.5% (1,002/1,200); male and female participants were of similar proportions, as indicated by 51.2% and 48.8%, respectively. A significant proportion of the participants (43.1%) disagreed that development partners have adequately contributed to the funding of sickle cell disease research in Nigeria. The majority of the respondents (81%) indicated that providing special funding for health research can facilitate access to healthcare services for sickle cell patients, whilst a similar proportion (79.2%) disagreed that the government alone bears the responsibility for healthcare initiatives for the disease. A third of the study participants (67.8%) were of the view that current research and development efforts towards sickle cell disease were inadequate.ConclusionThis study describes health professionals' views on access to healthcare for sickle cell, and the findings revealed the criticality of private and development sector funding in reducing the burden of the disease. Furthermore, capacity building at the primary healthcare level would not only ensure access to the basic healthcare needs of patients but could also demystify the condition.